A Large-Scale, Cross-Sectional Investigation Into the Efficacy of Brain Training - Hampshire, Adam; Sandrone, Stefano; Hellyer, Peter John (Frontiers in Human Neuroscience, 2019)
Brain training is a large and expanding industry, and yet there is a recurrent and ongoing debate concerning its scientific basis or evidence for efficacy. Much of evidence for the efficacy of brain training within this debate is from small-scale studies that do not assess the type of ‘brain training’, the specificity of transfer effects, or the length of training required to achieve a generalised effect. To explore these factors, we analyse cross-sectional data from two large Internet-cohort studies (total N=60,222) to determine whether cognition differs at the population level for individuals who report that they brain train on different devices, and across different timeframes, with programmes in common use circa 2010-2013. Examining scores for an assessment of working-memory, reasoning and verbal abilities shows no cognitive advantages for individuals who brain train. This contrasts unfavourably with significant advantages for individuals who regularly undertake other cognitive pursuits such as computer, board and card games. However, finer grained analyses reveal a more complex relationship between brain training and cognitive performance. Specifically, individuals who have just begun to brain train start from a low cognitive baseline compared to individuals who have never engaged in brain training, whereas those who have trained for a year or more have higher working-memory and verbal scores compared to those who have just started, thus suggesting an efficacy for brain training over an extended period of time. The advantages in global function, working memory, and verbal memory after several months of training are plausible and of clinically relevant scale. However, this relationship is not evident for reasoning performance or self-report measures of everyday function (e.g., employment status and problems with attention). These results accord with the view that although brain training programs can produce benefits, these might extend to tasks that are operationally similar to the training regime. Furthermore, the duration of training regime required for effective enhancement of cognitive performance is longer than that applied in most previous studies.